Nonvolatile Rewritable Photomemory Arrays Based on Reversible Phase‐Change Perovskite for Optical Information Storage. Issue 18 (29th May 2019) - Zou, Chen; Zheng, Jiajiu; Chang, Cheng; Majumdar, Arka; Lin, Lih Y.
Abstract: The high transmission speed of optical signals and their application in optical computation have created a growing demand for photon‐programmed memory devices. Rather than using electrical pulses to store data in one of two states, the photomemory (PM) devices exploit the optical stimulation to store the light information. In this work, the application of a nonvolatile rewritable PM array using the photochromic inorganic perovskite CsPbIBr2 grown by a vapor‐deposition process is demonstrated. Reversible phase transitions between orthorhombic (δ) and cubic (α) phases are achieved in CsPbIBr2 films through laser‐induced heat and moisture exposure. The PM pixels in an optically absorbing perovskite phase exhibit ≈50‐fold photoresponsivity as large as those in a transparent‐colored non‐perovskite phase. Storing optical data are achieved by heating pixels through a near‐infrared laser, while moisture exposure is used to erase the stored information. The nonvolatile PM array exhibits great write‐read‐erase cycle endurance and data retention capability without obvious performance degradation after storage in air for one week. This work demonstrates the promising application of vapor‐deposited inorganic perovskite for optical information storage and the unique potential of them for use in optical switches, tunable metasurfaces, and many other applications. Abstract : Vapor‐deposited all‐inorganic perovskite CsPbIBr2 can achieve the reversible phase transition between orthorhombic and cubic phases via heating and moisture exposure. These two phases feature distinct optoelectronic properties. A perovskite photomemory array is fabricated for a proof‐of‐concept application of the nonvolatile rewritable optical memory. The devices exhibit great stability over ten phase transition cycles without obvious performance degradation.